Multi-Factor Evaluation of RHL Success in Neniari Village, Indonesia - Lumapuy, Elvira; Matinahoru, Jhon. M.; Latumahina, Fransina (Indonesian Journal of Innovation Studies, 2024)
General Background: Forest and land rehabilitation (RHL) is essential for addressing critical land conditions, aiming to transform unproductive lands into areas that can enhance community living standards through increased productivity. Specific Background: In Neniari Village, the RHL program has been implemented with mixed success, utilizing agroforestry systems and involving various species, including both timber and non-timber plants. Knowledge Gap: Existing studies often lack detailed analysis of the factors influencing RHL success at a community and ecological level. Aims: This study seeks to evaluate the overall success of the RHL program in Neniari Village by considering plant survival rates, environmental factors, and community participation. Results: The survival rate of plants averaged 70%, indicating a moderate level of rehabilitation success, which did not meet the targeted benchmarks. Novelty: This research uniquely combines biotic and abiotic factor analyses with community engagement levels to assess RHL outcomes. Implications: The findings highlight the need for enhanced community involvement and improved environmental condition management to boost RHL success rates, suggesting adjustments to future rehabilitation strategies. Highlights: Community Involvement: Higher levels of community participation are directly linked to the success of rehabilitation efforts, indicating the need for more focused engagement strategies. Plant Survival: An average survival rate of 70% among various plant species underlines the challenges of RHL in achieving its goals, pointing towards the necessity for improved environmental management. Agroforestry Benefits: Utilizing agroforestry systems has shown potential benefits in enhancing ecological diversity and economic returns, suggesting its suitability for RHL practices. Keywords: Forest Rehabilitation, Community Participation, Agroforestry Systems, Plant Survival Rates, Environmental Factors